Antioxidant Activity and Potential Bioactive Peptides from Skin Protein Hydrolysate of Yellowfin Tuna (Thunnus albacares) - Sitti Hardiyanti Rachman; Joko Santoso; Sugeng Heri Suseno (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research